One Health: potential synergy between infectious and toxic agents. The case of COVID-19 - Jorge Herkovits (Academia Medicine)
Although the relationship between environmental toxicity and infectious diseases is poorly studied, it is probably more common than is recognized, since the chemical substances could be associated with pre-existing pathologies. For example, some conditions that influence the progression of COVID-19 could have toxicological causes such as cancer, endocrine, neurological, and inflammatory disorders, kidney failure, etc. This contribution highlights that SARS-CoV-2 and some high-volume organic and inorganic chemicals could also exert dysfunctions in the same homeostatic regulators such as HIF-1 and ACE2, with a potential synergistic effect that could affect the severity of COVID-19. This potential synergy is illustrated with adverse effects acquired through bioassays performed with free-living vertebrate embryos indicating that their use as sentinel organisms for environmental contamination could be beneficial both for the ecosystem and human health.